Physical, Chemical and Organoleptic Characteristics of Red Dragon Fruit Instant Drink Powder (Hylocereus polyrhizus) - Kasih Ayu Wulansari; Lukman Hudi; Ida Agustini Saidi (Universitas Muhammadiyah Sidoarjo, 2022)
Red dragon fruit is the type of dragon fruit that is most in demand by consumers because it is more nutritious for the health of the body. The production of red dragon fruit every season is always abundant. However, fresh dragon fruit cannot be stored for long, because it has a high moisture content of 90%. Therefore, it is necessary to carry out further processing so that nutritional needs can be maintained and extend the shelf life by making instant drink powder using the foam mat drying method. This study used the Split Plot Design method with the basic design of RAK (Randomized Block Design) which was repeated 3 times, with drying temperature treatment as the main plot consisting of 3 levels, namely 40°C, 50°C, 60° C and treatment with maltodextrin concentration as sub-plots consisting of 3 levels, namely 10%, 15%, 20%. The data were analyzed by analysis of variance and then continued with the Honest Significant Difference (BNJ) test at a 5% level and the hedonic scale organoleptic test. The results showed that the highest value of the solubility parameter was 68.68%, water content 8.08%, vitamin C 11.11%, color organoleptic 4.10, taste organoleptic 3.90, aroma organoleptic 3.67.